Активная зона высокотемпературного ядерного реактора на тепловых нейтронах с твердым мелкодисперсным теплоносителем - Гаврилов П. М. Петр Михайлович; Денискин В. П. Валентин Петрович; Дмитриев А. М. Александр Мефодьевич; Наливаев В. И. Владимир Иванович; Федик И. И. Иван Иванович
опубл. 20.01.08